Engagement of Neurotropic Viruses in Fast Axonal Transport: Mechanisms, Potential Role of Host Kinases and Implications for Neuronal Dysfunction - Richards, Alexsia; Berth, Sarah H.; Brady, Scott; Morfini, Gerardo (Frontiers in Cellular Neuroscience, 2021)
Much remains unknown about mechanisms sustaining the various stages in the life cycle of neurotropic viruses. An understanding of those mechanisms operating before their replication and propagation could advance the development of effective anti-viral strategies. Here, we review our current knowledge of strategies used by neurotropic viruses to undergo bidirectional movement along axons. We discuss how the invasion strategies used by specific viruses might influence their mode of interaction with selected components of the host’s fast axonal transport (FAT) machinery, including specialized membrane-bounded organelles and microtubule-based motor proteins. As part of this discussion, we provide a critical evaluation of various reported interactions among viral and motor proteins and highlight limitations of some in vitro approaches that led to their identification. Based on a large body of evidence documenting activation of host kinases by neurotropic viruses, and on recent work revealing regulation of FAT through phosphorylation-based mechanisms, we posit a potential role of host kinases on the engagement of viruses in retrograde FAT. Finally, we briefly describe recent evidence linking aberrant activation of kinase pathways to deficits in FAT and neuronal degeneration in the context of human neurodegenerative diseases. Based on these findings, we speculate that neurotoxicity elicited by viral infection may involve deregulation of host kinases involved in the regulation of FAT and other cellular processes sustaining neuronal function and survival.